Construction of a Family of Minimal Helicoid Surfaces Passing Through an Isoparametric Helix Curve - Ridwan Prawira Yunaldi; Haripamyu Haripamyu; Efendi Efendi (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2026)
This research concerns the construction of a family of minimal surfaces passing through a helical curve. The construction follows the research by Yoon, which employs an approach using the curvature and torsion functions of a given curve. The construction yields a family of generalized helicoids as the minimal surfaces passing through the helical curve.